Edukasi Pembuatan Teh Celup Bunga Telang Dengan Penambahan Jahe Dan Serai Di Kelurahan Rawa Makmur RT 09 Kecamatan Muara Bangkahulu Kota Bengkulu - syaida, Femmi Muhar; Sari, Anjelia Puspita; Saputra, Febry Dian; Dwi S, Muhammad Efrizal; Widawati, Lina; Meisya, Hilda; Afriani, Ririn (Jurnal Dehasen Mengabdi, 2025)
Kelurahan Rawa Makmur RT 09 Muara Bangkahulu District is one of the areas in Bengkulu City, where the majority of the livelihoods are laborers and traders. Currently in Rawa Makmur RT 09, especially the PKK women are empowering ornamental plants, namely telang flowers. Besides being an ornamental plant, the flowers have health benefits and have the potential to be processed as herbal drinks. Telang flowers are blue, purple or purplish blue in color which comes from anthocyanin compounds. The compound is beneficial for health because it has antioxidant activity. Anthocyanins found in telang flowers have good stability, so they are often used as natural dyes in food. Apart from being a colorant, the anthocyanin content in telang flowers has a function as a source of antioxidants that function as an antidote to free radicals in the body. Tea is a raw material for refreshing drinks that is widely known and favored by people around the world. Currently, various kinds of herbal teas have been developed, such as spice tea, moringa tea, and telang flower tea, which contain many antioxidants that are good for the body. Telang flower herbal tea has the disadvantage that the aroma of telang flowers is less favorable when brewed. Therefore, to produce flavorful tea, additional ingredients are needed that can be used as aroma enhancers, such as pandan leaves, ginger rhizomes, and lemongrass stems.